Swinging The Pendulum Towards Social Emotional Support (A Position Paper) - Jessica Lane (The Advocate, 2018)
This paper discusses how for 15 years mandated high-stakes testing took precedence as the prominent measure of student success. An unintentional consequence of this time was that social-emotional competencies were overlooked. Most recently, the Kansas Department of Education (KSDE) has developed and implemented an accreditation model that is based off of a more holistic look at student success. This new model broadens the scope of academic success, and uses the ideas of relationships, relevance, responsive culture, rigor, and results as key measurable components. This article posits that leveraging the expertise of school counselors in social and emotional development, and providing support for classroom teachers is paramount to the success of this accreditation model and initiative.